Аналіз динаміки запірно-врівноважуючого пристрою ротора багатоступінчатого відцентрового насоса для турбулентного режиму руху рідини - Павленко, Іван (КІНПАТРІ ЛТД, 2013)
The solution of the problem of the stress-strain state of the lock joint of a number of the operating blades of the steam turbine in an elastic formulation is presented. Also, the results of research in the form of the field of the stress, strain and contact pressure at the reference sites of the lock joint are presented.
Dynamic analysis of the locking automatic rotor-balancing device of the multistage centrifugal pump for a turbulent fluid motion